Measurement of the electroweak production of Z gamma and two jets in proton-proton collisions at root s=13 TeV and constraints on anomalous quartic gauge couplings - (:unkn) unknown (AMER PHYSICAL SOC, 2021)
The first observation of the electroweak (EW) production of a Z boson, a photon, and two forward jets (Z gamma jj) in proton-proton collisions at a center-of-mass energy of 13 TeV is presented. A data set corresponding to an integrated luminosity of 137 fb(-1), collected by the CMS experiment at the LHC in 2016-2018 is used. The measured fiducial cross section for EW Z gamma jj is sigma(Ew )= 5.21 +/- 0.52(stat)+/- 0.56(syst) fb = 5.21 +/- 0.76 fb. Single-differential cross sections in photon, leading lepton, and leading jet transverse momenta, and double-differential cross sections in mjj and vertical bar Delta eta(jj)vertical bar are also measured. Exclusion limits on anomalous quartic gauge couplings are derived at 95% confidence level in terms of the effective field theory operators M-0 to M-5, M-7, T-0 to T-2, and T-5 to T-9.